2020
DOI: 10.1002/bsl.2488
|View full text |Cite
|
Sign up to set email alerts
|

The dark figure of sexual offending: A replication and extension

Abstract: Studies of the dark figure of sexual offending using federal correctional clients reported significant evidence of previously unknown or hidden sexual violence, often among clients with no official criminal history. Unfortunately, research has produced variable estimates of how large the dark figure is. The current study sought to replicate recent studies of federal sexual offenders about the dark figure of sexual offending. We also extended the knowledge base by providing additional correlational analyses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Some researchers have concluded that online child pornography offenders are primarily interested in fantasizing about children as sexual objects [12,13,18]. These individuals have little desire to engage in the physical world with children in a sexual manner despite their fantasies and pose a low risk of contact [2,6,29]. Online child pornography offender's activities are "online" and primarily centered around the collecting (possessing) of CSEMs (CSEM) that add to or enhance their fantasies [2,6,13].…”
Section: Online Child Pornography Offendersmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have concluded that online child pornography offenders are primarily interested in fantasizing about children as sexual objects [12,13,18]. These individuals have little desire to engage in the physical world with children in a sexual manner despite their fantasies and pose a low risk of contact [2,6,29]. Online child pornography offender's activities are "online" and primarily centered around the collecting (possessing) of CSEMs (CSEM) that add to or enhance their fantasies [2,6,13].…”
Section: Online Child Pornography Offendersmentioning
confidence: 99%
“…Other studies have indicated that online child pornography offenders may still be motivated by a sexual interest in children and that often their previous contact offenses have not been identified [29,30].…”
Section: Online Child Pornography Offendersmentioning
confidence: 99%
“…In this line, the #metoo movement of 2017 highlighted the sexual assaults experienced daily by hundreds of women in the workplace, the impact of which brought about the creation of a series of regulations on labor matters to promote a harassment-free work environment in different organizations around the world [ 10 , 11 ]. In addition to this figure, we must consider “the dark figure” of sexual aggressions, which according to several international studies is estimated to be between 10 to 20.5 times higher than that reported [ 12 , 13 , 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…Another difficulty in the analysis of this phenomenon lies in the absence of official records regarding these crimes, as well as the presence of a "dark figure" that keeps information about these types of attacks from being discovered (Drury et al, 2020). Also, and although this dark side of crime is common to all criminal offences (Levan Miller, 2010), the nature of sexual offences produces a series of negative reactions in the victims (anger, shame, guilt) that prevent them from reporting the attack (Jones et al, 2009).…”
Section: Introductionmentioning
confidence: 99%